The development of a STEM-based e-Module to help fifth-grade pupils strengthen their creative thinking skills in the topic of My Blood Circulation - Desak Ketut Rani Astiti Asih; Sunyono Sunyono; Dwi Yulianti; Doni Andra (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
Technology and education are now required for the development of 21st century skills. The purpose of this study was to determine 1) the practicality of STEAM-based e-Modules in online learning, 2) the importance of STEAM-based e-Modules in online learning, and 3) the improvement of students' creative thinking skills in fifth grade on the content "My Blood Circulation is Healthy." A total of 16 students were employed in the study. Questionnaires and tests were utilized as data gathering instruments. Problem and need analysis, literature review, product design, validation, and practitioner testing were the stages of development. The findings revealed that pupils' low creative thinking abilities were attributed to teachers' failure to adequately embrace technology and their continued usage of traditional instructional materials. The STEAM-based e-Module development improved creative thinking skills of Grade 5 students.